(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 09:44:38
(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的(a^2
(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的
(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)
求过程,简单易懂,谢谢哒,快一点的
(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的
原式=(a^2b)^3m÷(a^2b)^(7m-4m)=(a^2b)^3m÷(a^2b)^3m=1
(a-b)^m+3(b-a)^2(a-b)^m
(a-b)^5m(b-a)^2m÷(b-a)^7m
(a-b)^3m*(b-a)^2m÷(b-a)^5m
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
计算:(b-a)^5(a-b)^m+(a-b)^(m+3)(b-a)^2
计算:(a-b)^m+3(b-a)^2(a-b)^m(b-a)^5
-12a^2m-1b^m+1+20a^m-1b^2m+3
若m^2-3m+2=(m+a)(m+b)则a= b=
(a+b)m^2-(b+a) 因式分解....................
m^2(a+b)-a-b因式分解
计算:(a-b)^(m)*(a-b)^(2)*[2(b-a)]^3*[(b-a)^(5)]^(2)/(a-b)^(m).
(a-b)^m*(a-b)*[2(b-a)^3*(b-a)^5]^2/(a-b)^m怎么做?
(a^2b)^3m÷((a^2b)^7m÷(a^2b)^4m)求过程,简单易懂,谢谢哒,快一点的
若a^7*b^5÷a^m-1*b^n+1=a^2n-3*b^m+5,求m-n
若a^7*b^5÷a^m-1*b^n+1=a^2n-3*b^m+5,求m-n 速度了
[6a^(m+2)b^(n+2)-4a^(m+1)b^(+1)+2a^(m)b^m]÷(-2a^(m)b(n)
(a-b)(m-2n)+(b-a)(2m-n)
分解因式a^2(m-b)(m-c)(c-b)+b^2(m-c)(m-a)(a-c)+c^2(m-a)(m-b)(b-a).在线等.